Running for Recovery: Marathons of the Body, Mind, Spirit (Toplink Publishing, LLC, 2018)
In a physical marathon, the "wall" shows up about mile twenty or twenty-one; when this happens, mind and body shake hands to say "we quit." That's where most runners will shut down, unless they reach down into their identity as spirit. To the question "Who am I; what is my identity?" God's answer is "I am spirit; I have a mind; and I live in a body." So, to break through the "wall" requires a hierarchy of spirit over mind over body. God's Word will address our spirit when mind and body are out of it, thereby setting Word over spirit over mind over body to keep the feet moving. Project this to other marathons: mental, spiritual, emotional, interpersonal, occupational, financial, etc. Bottom line: Can the reader finish the book, put it down, and say, "Wow, look what God's Word performed; I want to be in the Word; I want the Word to be in me"? The closer the reader comes to God's Word, the closer they come to Him (John 1:14). The Word will have become "sent out (Isaiah 55:10-11), active and alive (Hebrews 4:12), watched over and performed" (Jeremiah 1:12) in their lives!

Blueprint for Holistic Healing: Your Practical Guide to Body-Mind-Spirit Health (A.R.E. Press, 2016)
Dr. Shealy was first introduced to the work of the "father of holistic medicine," Edgar Cayce, in the early 1970's. Cayce was the inspiration for his transformation from traditional medicine to holistic alternative therapies, which he has pursued for more than 30 years. Now combining decades of clinical work and research with advice from the Edgar Cayce readings, Shealy has created a blueprint for healing that each of us can follow with questionnaires for self-assessment throughout.

Transpersonal medicine: the new approach to healing body-mind-spirit (Shambhala, 1996)
Description Not Provided

Aromatherapy for life empowerment: using essential oils to enhance body, mind, spirit well-being (Basic Health Publications, 2011)
Description Not Provided

The live food factor: the comprehensive guide to the ultimate diet for body, mind, spirit & planet (Awakenings Publications, 2008)
Description Not Provided

Hippie Family Values (New Day Films, Kanopy Streaming, 2018)
An intimate chronicle of hippie elders and their adult children, filmed over a 10-year period at a communal ranch in New Mexico. The founders of this back-to-the-land experiment are slowing down and facing declining health. Will the next generation be able to sustain the community?. The film counters dismissive stereotypes with stories of people whose worldview was forged in the 60s counterculture, and who remain motivated by those youthful ideals in their 60s, 70s and 80s-a vision, more urgent now than ever, of healed relationships to body, mind, spirit, society, Earth and cosmos.. "A beautiful film, told with such sensitivity, integrity, and respect" - Sonali Gulati, Virginia Commonwealth University

The art of Jin Shin: the Japanese practice of healing with your fingertips (Tiller Press, Simon & Schuster Audio, 2019)
"Balance your body, mind, and spirit and heal yourself with your own hands using this clear, step-by-step illustrated guide to the practice of the ancient Japanese healing art of Jin Shin--written by a trained expert with nearly three decades of experience. You might be surprised to learn that the majority of today's most common ailments including anxiety, backaches, colds and flu, digestive issues, immune disorders, migraines, and insomnia, can be alleviated naturally by restoring and harmonizing blocked, stagnant energy. The art of Jin Shin, based on the Japanese healing art of energy medicine, is practiced throughout the world. While related to acupressure and massage therapy, this holistic practice uses only minimal pressure and gentle touching withthe fingers and hands to redirect or unblock the flow of energy along the body's fifty-two points (twenty-six on each side of the body)--called Safety Energy Locations, or SELs--areas where energy tends to get congested. This simple, non-invasive processallows your body's energy to flow smoothly, and with balance restored, you will experience a sense of wellbeing and calm. The Art of Jin Shin explains all the basics of this healing art and provides you with the knowledge you need to practice it on yourself--with exercises ranging from simply holding a finger for a few minutes to spending twenty minutes to harmonize a specific circulation pattern. Whether you desire a deeper understanding of the body/mind/spirit connection or want to create a daily Jin Shin maintenance routine the power is literally at your fingertips"-- "Jin Shin Jyutsu: Healing at Your Fingertips is a complete self-help guide to the practice of the ancient Japanese healing art that balances body, mind and spirit by using our hands. Illustrated throughout and written by a trained Jin Shin Jyutsu practitioner with 25 years of experience, the book will appeal to the growing market of people turning to holistic treatments that complement Western medicine for pain and common afflictions such as anxiety, stress, and insomnia"--

The soul searcher's handbook: the modern girl's guide to the new age world (Beyond Words, 2015)
From aromatherapy and numerology to healing crystals and meditation, this fun and sassy guide to everything body-mind-spirit defines New Age practices for a new generation. What type of crystal should I put in my car for a road trip? Should I Feng Shui my smart phone screen? In this illuminating introduction for the modern-day soul searcher, Emma Mildon shines light on everything your mom didn't teach you about neo-New Age practices. With something for every type of spiritual seeker, The Soul Searcher's Handbook offers easy tips, tricks, and how-tos for incorporating everything from dreamology and astrology to mysticism and alternative healing into your everyday life. This handbook is your #1 go-to guide--handy, accessible, entertaining, and packed with all the wisdom you need in one place. Your destiny, gifted to you at birth, is waiting. So plug into the universe, dig your toes into the soil of Mother Earth, and open your soul to your full potential. Regardless of what you're seeking, The Soul Searcher's Handbook is your awakening to a more fulfilling and soulful life.
Healthy body , Your body balance , Your crystals and gemstones , Your aromatherapy , Your soul, Chakras, and auras , Your Feng Shui , Awakened mind , Your dreams , Your numerology and name , Your astrology , Your universal laws , Vibrant spirit , Your guides , Your Akashic records and past lives , Your light council and soul mates , Your protection ceremonies , Your celebration , Your soul search.